Pripovedi spolnih manjšin v Sloveniji po letu 2000 - Zupan Sosič, Alojzija (Jezik in slovstvo, 2018)
Twenty-nine narrative books written by sexual/gender minorities have been published in Slovenia since 2000. The present study analyses just one text by each of the following authors: Brane Mozetič, Nataša Sukič, Suzana Tratnik, Gojmir Polajnar (Boris Pintar), Urška Sterle, Jedrt Lapuh Maležič, Vesna Lemaić, Teja Oblak and Nina Dragičević. An interpretative analytical approach combined with the starting points of gay and lesbian studies and queer theory found the following novelties in the LGBTQ narrative of the new millennium: the dominance of lesbian topics, the emergence of transsexual characters, the erosion of victimisation, and subversion as modernisation of the narrative level.
Keywords: lezbične teme; literarne študije; slovenska književnost; slovenske pisateljice; slovenski pisatelji; spolne manjšine; transspolni liki